Mechanism of Beraprost Effects on Pulmonary Hypertension: Contribution of Cross-Binding to PGE2 Receptor 4 and Modulation of O2 Sensitive Voltage-Gated K+ Channels - Fan, Fenling; Tian, Hua; Geng, Jie; Deng, Jizhao; Liu, Ya; Chen, Chunyan; Zhang, Songlin; Zhang, Yushun; Li, Jie; Tian, Hongyan; Dart, Anthony M.; Zou, Yuliang (Frontiers in Pharmacology, 2019)
Background: The purpose of this study is to elucidate mechanism(s) by which the orally active PGI2 analog, Beraprost (BPS), ameliorates pulmonary hypertension (PH). Prostaglandins are an important treatment for PH. Mechanisms of their action are not fully elucidated in relation to receptor subtype and effects on O2 sensitive Kv channels. Methods: Distal (3rd order and beyond) pulmonary arteries from chronically hypoxic rats and from humans with established PH were studied. Measurements included pulmonary haemodynamics and histology, vascular reactivity, prostanoid receptor expression and activity of the O2 sensitive Kv channels. Results: Prostacyclin receptor (IP), prostaglandin receptor E3 (EP3) and prostaglandin receptor E4 (EP4) are the main pulmonary artery receptor subtypes in both rat and human pulmonary arteries. Circulating levels of PGI2 and PGE2 were reduced in PH. PH was also associated with reduced receptor expression of IP but not of EP4. The effects on IP expression were overcome with BPS. Dilatory responses in PH to BPS were reduced in the presence of EP4 blockade. Expression and activity of oxygen sensitive Kv channels were reduced in pulmonary artery smooth muscle cell from rats with PH and humans with PAH and were also overcome by administration of BPS. Effects of BPS on oxygen sensitive Kv channels were reduced in the presence of EP4 blockade implicating the EP4 receptor, as well as the IP receptor, in mediating BPS effects. Conclusion: Reduced expression of pulmonary IP receptors and reduced activity of O2 sensitive Kv channels are found in PH in both humans and rats. The orally active prostacyclin analogue, BPS, is able to reverse these changes, partly through binding to the EP4 receptor.